IRE Teachers’ Perceptions and Prevention of Student Sexual Deviance in Bandung High Schools - Salis Salis; Wawan Hermawan; Agus Fakhruddin (Universitas Muhammadiyah Mataram, 2026)
The phenomenon of risky sexual behavior in contemporary urban settings has undergone a significant shift due to the normalization of digital culture. This study aims to explore Islamic Religious Education (IRE) teachers' perceptions of adolescent sexual behavior and to examine the strategic measures undertaken to mitigate it within senior high school contexts. Employing a descriptive qualitative approach, data were collected through in-depth interviews with seven IRE teachers in Bandung, Indonesia, selected via purposive sampling. Data were analyzed using the Miles and Huberman interactive model, involving data reduction, data display, and conclusion drawing to ensure analytical rigor. The findings reveal a normative–religious framework categorizing adolescent dating as sexual deviance based on the sadd al-dharī‘ah (blocking the means to sin) principle. Crucially, this study identifies a Parental Paradox, where parents permit heterosexual dating to prevent perceived greater deviations like LGBT. While teachers implement religious habituation and environmental engineering, effectiveness is hindered by a professional competence gap in psychological counseling. This study advocates for shifting IRE toward a religiously sensitive counseling model. Practically, educational authorities must integrate adolescent psychological competencies into the IRE curriculum to address contemporary sexuality issues more transformatively.